O sopro do vazio - Ferreira, Helena Isabel Santos, 1973- (2017)
The relation between emptiness and creation was the motivation for my research. This master thesis in painting, in practical-theoretical style, started from the artistic-practice and from the necessity of a deeper dedication for the understanding of some concepts considered useful for the evolution of the practical work. The starting point was the period of the beginning of abstraction, considered as the historical period when the picture released from its illustrative function, evolved, expanded and contaminated other expressive/artistic areas. Questions related to my artistic work and subjects of immaterial nature, like emptiness and creation, were always present. Therefore, I had to look for foundations in philosophy and religion. This tendency of mine is characteristic of contemporary spirituality and reflected through art. The artistic contemporary spirituality is an alternative to religion and is behind the work of innumerous artists. Paul Klee, Wassily Kandinsky, Mark Rothko, Yves Klein, Henry Moore, Antoni Tàpies, Álvaro Lapa and Rui Chafes, are some of the reference artists for both my work of research and artistic. The spontaneousness in artistic creativeness is a dominant factor in my work, and starting from emptiness is always the beginning of the work process and a motivating strategy. I begin steadily from a “zero point”, through embryonic forms, and without support of already existing images or previous studies. However, there is a permanent attitude of study and forms captivation, of testing of materials and techniques, of colour work, of development of ideas on themes which, not being directly related with specific works, reflects itself in all work done. Parallelly to this attitude, I also practice the improvisation and valuation of creative cases that are the result of emptiness that happens often in the artistic experience